D04 A Study Of The Hypothalamo-pituitary Axes In Huntington's Disease. (17th September 2014) - Silajdžić, E; Kalliolia, E; Nambron, R; Costelloe, S; Martin, N; Hill, NR; Frost, C; Watt, H; Hindmarsh, P; Björkqvist, M; Warner, TT
Abstract : Background: Huntington's disease (HD) patients often exhibit debilitating symptoms such as sleep disturbances, muscle atrophy and weight loss. These symptoms may be linked to progressive hypothalamic pathology and dysfunction of hypothalamo-pituitary axes. Aims: Our aim was to study neuroendocrine profiles of hypothalamo-pituitary axes hormones in healthy controls, premanifest and stage II/III HD subjects. Methods: We quantified adrenocorticotropic hormone (ACTH), cortisol, luteinizing hormone (LH), follicle stimulating hormone (FSH) and growth hormone (GH) over a 24-hour period in 15 healthy controls, 14 premanifest and 13 stage II/III HD subjects. We also quantified fasting levels of vasopressin, oestradiol, testosterone, dihydroepiandosterone sulphate, thyroid stimulating hormone, free triiodothyronine, free total thyroxin and prolactin. In addition, growth hormone releasing factor, insulin-like growth factor-1 and insulin-like factor binding protein-3 were quantified at 06:00, 15:00 and 23:00. A battery of clinical tests, including neurological rating and function scales, were also performed. Results: 24-hour concentrations of ACTH, cortisol, LH and FSH did not differ significantly between the HD group and controls. The daytime GH secretion was similar in control and HD subjects, however, there was a significant reduction in the post-sleep GH pulse in stage II/III HD compared to healthy controls. In HD subjects, baseline levels of most of the hypothalamo-pituitary axis hormones quantified did not significantly differ from those in healthy controls. Conclusions: Reduced post-sleep GH secretion in HD subjects may reflect sleep disturbances and suggests somatotropic axis dysfunction in HD, which may contribute to symptoms in HD patients. Contrary to previous studies that showed altered levels of hypothalamo-pituitary hormones in patients with HD, most of the hormones measured in this study were unaltered.